2018
DOI: 10.1186/s13104-018-3989-y
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli bacteriuria in pregnant women in Ghana: antibiotic resistance patterns and virulence factors

Abstract: ObjectivesThe relevance of Escherichia coli associated bacteriuria infection in pregnant women is poorly understood, despite these strains sharing a similar virulence profile with other pathogenic E. coli causing severe obstetric and neonatal infections. We characterized and determined the antimicrobial susceptibility, resistance genes and virulence profiles of 82 E. coli isolates associated with asymptomatic bacteriuria in some pregnant in Ghana from February to August 2016 using Kirby–Bauer disc diffusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
16
6
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 50 publications
(49 reference statements)
16
16
6
5
Order By: Relevance
“…papC, papGII and ecp (A and RB) _ the other genes related to the ability to colonize the urinary tract epithelium were detected in 88.5% , 14.2% and 58.1% of the isolates, respectively. Our results are in agreement with those found by other studies [17,[18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…papC, papGII and ecp (A and RB) _ the other genes related to the ability to colonize the urinary tract epithelium were detected in 88.5% , 14.2% and 58.1% of the isolates, respectively. Our results are in agreement with those found by other studies [17,[18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with previous studies [24]. This study showed a considerable number of bacteria to harbor the kpsMTII, fimH, papC, iutA, fyuA, traT and sfa/focDE, respectively, which was in contrast to Sáez-López et al, but in line with Forson et al study on pregnant women in Barcelona [23] and Ghana [18].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations